Penerapan Model Pembelajaran Means End Analysis (MEA) Dalam Setting Di Untuk Meningkatkan Hasil Belajar Siswa - Juniyarti, Nina (Berkala Ilmiah Pendidikan Fisika, 2014)
The low analysis skills of the student to science materials resulted in lower learning outcomes. Therefore conducted research to increase learning outcomes of the student with learning models MEA. Specific objectives of this research to describe: (1) implementation lesson plan, (2) analysis skills, (3), learning outcomes, (4) students interests. This research uses classroom action research consisted of 3 cycles. Research subjects were 26 students. Data obtained from learning outcomes tests, observations, questionnaires,  and documentation. Analyzed data from the qualitative description and quantitative description.  The result of research showed that  (1) implementation lesson plan on cycle I 85,55%, cycle II 87,15% and cycle III 92,72% and categorized very well, (2) analysis skills on cycle I 56,86%, cycle II 75,58%, and cycle III 80,93% and categorized very well. (3) enhancement completeness learning outcomes of the student in the classically on cycle I 15,34% (not completed), cycle II 85,0% (complete), and cycle III 100% (complete), (4) students interests in general classified good. We conclude that application of learning models MEA can increase learning outcomes of student class of X-H MA Negeri 2 Model Banjarmasin on the subject of heat transfer.